More process patterns : delivering large-scale systems using object technology - Ambler, Scott W., 1966- (Managing object technology series ;, 1999)
With his new book, More Process Patterns, Scott Ambler picks up where Process Patterns left off. In this book, the author presents process patterns for the second half of the development lifecycle. He covers the Deliver phase and the Maintain and Support phase of large-scale, object-oriented system development. Each presented pattern is based upon proven, real-world techniques and is geared toward medium to large-size organizations who need to develop software internally to support their main line of business. The book covers major management issues, such as people and risk management, and quality assurance. Developers and project managers who have just taken their first OO development course will find this book essential. It takes the true needs of software development and delivery into consideration, including cross-project, maintenance, operations, and support issues. This book uses the Unified Modeling Language (UML).